Strategy and Coopetitive Relationships: the case of Nova Serrana cluster - Leite, Ramon Silva; Lopes, Humberto Elias Garcia; Silva, Suelen Aparecida Duarte (Review of Business Management, 2009)
Traditionally, the management literature discusses the effects of competitive or collaborative relationships in organizational strategy. However, recently a third approach has emerged, in which a single relationship is seem as a variable that can integrate collaboration and rivalry between competitors. This study aims to provide subsidies for this discussion. For this, a qualitative design was adopted; in which businessmen of the city of Nova Serrana were interviewed. The results indicate that the decision of collaborate or compete is dependent on a set of factors. Key words: Coopetition. Relationships. Competition.